A review of adversity, the amygdala and the hippocampus: a consideration of developmental timing - Tottenham, Nim; Sheridan, Margaret A. (Frontiers in Human Neuroscience, 2010)
A review of the human developmental neuroimaging literature that investigates outcomes following exposure to psychosocial adversity is presented with a focus on two subcortical structures – the hippocampus and the amygdala. Throughout this review, we discuss how a consideration of developmental timing of adverse experiences and age at measurement might provide insight into the seemingly discrepant findings across studies. We use findings from animal studies to suggest some mechanisms through which timing of experiences may result in differences across time and studies. The literature suggests that early life may be a time of heightened susceptibility to environmental stressors, but that expression of these effects will vary by age at measurement.